Textual production in the School environment: the application of Vygotsky’s Theory of Mediation (Research, Society and Development, 2020)
This work aims to present a pedagogical proposal, in the format of a didactic sequence, aiming at the textual production activity, in line with Vygotsky's Theory of Mediation. A bibliographic review was carried out on the mentioned Theory and a study on the need to re-signify the activity 'textual production' in the school environment, in order to subsidize the proposal to be presented. This proposal aims to develop the potential of individuals regarding critical expressiveness through written language, having an important contribution from the conceptions of Vygotsky's Theory, which considers the importance of the teacher's role as a mediator of the learning process, acting in the space between what the student already knows and what he may come to know, that is, intervening in favor of reaching his full potential. If applied properly, the activity can be an important tool to achieve the full condition of the individual to express himself critically, developing skill with writing and opening space for effective participation in the issues of the reality that surrounds him.